Evaluation of Acid and Hydraulic Fracturing Treatment in Halfaya Oil Field-Sadi Formation - Al-Sudani, Jalal Abdulwahid; Husain, Khalid Munaf (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Sadi formation is one of the main productive formations in some of Iraqi oil fields. This formation is characterized by its low permeability values leading to low production rates that could be obtained by the natural flow. Thus, Sadi formation in Halfaya oil field has been selected to study the success of both of "Acid fracturing" and "Hydraulic fracturing" treatments to increase the production rate in this reservoir. In acid fracturing, four different scenarios have been selected to verify the effect of the injected fluid acid type, concentration and their effect on the damage severity along the entire reservoir. The reservoir damage severity has been taken as "Shallow–Medium– Severe" and (Medium–Severe-sallow) for better fluid invasion. While, in hydraulic fracturing, a three cases have been selected using three different main fracturing fluid and three different proppant size and types, to verify their effects on fracturing efficiency, and dimensionless fracture conductivity. The results show that both treatments have successful results, but the hydraulic fracturing gives about (1.5) times greater than acid fracturing. However, the maximum dimensionless fracture conductivity reached by all the treatments was about (Fcd = 4) , with fracture efficiency reached to (82%).